Priscillian, a Western Christian with an Origenian Culture - Sanchez, Sylvain Jean Gabriel (Gerión. Revista de Historia Antigua, 2021)
Priscillian was not a follower of Origen of Alexandria. Yet, his writings show the influence of both the secrets of the heavenly world and the godly names, as transmitted by Origen. Priscillian had access to Origen’s works either directly in Greek or Latin in a pre-rufinian version or indirectly through the works of Hilary of Poitiers, or else thanks to a monk coming from Egypt who was a follower of Origen and exiled in Hispania under the protection of Melania the Elder. In the light of recent work, this study aims to deepen the substrate of a biblical tradition which Priscillian’s christianism would have inherited through Origen.
Keywords: Judeohellenism; Biblical Exegesis; Mysticism; Christian Esoterism; Heresiologism; Patristic Literature